Pulpal Responses to Leukocyte- and Platelet-Rich Plasma Treatment in Mouse Models for Immediate and Intentionally Delayed Tooth Replantation - Angela Quispe-Salcedo; Kiyoko Suzuki-Barrera; Mauricio Zapata-Sifuentes; Taisuke Watanabe; Tomoyuki Kawase; Hayato Ohshima (Applied Sciences)
This study aimed to evaluate the effect of leukocyte and platelet-rich plasma (L-PRP) on the pulpal healing process following immediate and intentionally delayed tooth replantation in mice. After the maxillary first molars of 3-week-old mice were extracted, the teeth were immersed for 1 min [immediate reimplantation (IR)] or 30 min [intentionally delayed reimplantation (IDR)] in phosphate-buffered saline (PBS) solution. The alveolar socket was filled with or without 1.5 μL of L-PRP [experimental or control groups (EG or CG)] followed by tooth replantation. Samples were collected from day 1 to week 4 after the operation, processed for histology, and evaluated by immunohistochemistry for Nestin and Ki-67 expression. Quantitative analysis revealed positive Nestin staining during pulpal healing in the EG at week 1 following IR and week 2 following IDR. Hard tissue deposition was significantly increased in the EG after IR at week 2. Cell proliferation was higher in the EG compared with that in the CG at week 1 and significantly decreased in the coronal pulp of the EG after the IDR at week 2. Our data suggest that treatment with L-PRP may have a positive effect on pulpal healing, even in teeth replanted after an extended extra-oral period.